2020
DOI: 10.1021/acsami.9b21331
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of FTO/TiO2 Substrates: Route toward Simultaneously High-Performance and Cost-Efficient Carbon-Based, All-Inorganic CsPbIBr2 Solar Cells

Abstract: Carbon-based, all-inorganic perovskite solar cells (PSCs) have drawn enormous attention recently on account of their ungraded stability and reduced costs. However, their power conversion efficiencies (PCEs) still lag behind the ones with conventional architecture. Moreover, the high cost of FTO substrates and energy-consuming sintering process of TiO 2 electrontransporting layers should be further addressed. Herein, it is demonstrated that the FTO/TiO 2 substrates could be separated simply from degraded CsPbIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 60 publications
2
49
0
1
Order By: Relevance
“…There still exist residual perovskite-derived species on the recycled ITO/TiO 2 substrates. 13,44 Here we found, using this amineinvolved nonpolar solvent system, that there is no residual perovskite remaining at the SnO 2 surface. This could be ascribed to the strong insertion ability of the amine molecule into the perovskite lattice that can quickly liquefy the perovskite and detach it from the substrate.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…There still exist residual perovskite-derived species on the recycled ITO/TiO 2 substrates. 13,44 Here we found, using this amineinvolved nonpolar solvent system, that there is no residual perovskite remaining at the SnO 2 surface. This could be ascribed to the strong insertion ability of the amine molecule into the perovskite lattice that can quickly liquefy the perovskite and detach it from the substrate.…”
Section: Resultsmentioning
confidence: 56%
“…This multi-step process led to the reuse of the TiO 2 -coated FTO substrate and perovskite precursors comprising PbI 2 and MAI for fabricating new solar cells. Recently, Zhu et al 13 employed similar chemicals, using DMF to dissolve the all-inorganic CsPbIBr 2 perovskite, and recycled the FTO/glass for reuse. Chhillar et al 14 demonstrated that degraded perovskite (with a rich PbI 2 phase) could be recovered back to tetragonal perovskite, which can help in minimizing the waste from failed devices to a certain degree.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…In their case, they recycled the FTO TiO 2 glass from perovskite cells. They removed the top layers of the perovskite cell and applied fresh CsPbIBr 2 and carbon layers [40]. TiO 2 is commonly used in DSSCs because it is the best trade of between sustainability and efficiency [41].…”
Section: Using Recycled Materials To Build Dsscsmentioning
confidence: 99%
“…However, Zhang and coworkers [ 156 ] came to a different conclusion in all‐inorganic PSCs based on CE where pinholes were favorable for suppressing carrier nonradiative recombination through forming desirable crystalline grains, The device based on CsPbIBr 2 films with benign pinholes yielded a PCE of 9.06%, which was much higher than 6.19% of the reference device without pinholes. Zhang and coworkers [ 155 ] developed a recycle strategy which enabled the simultaneous achievement of PCE enhancement and cost saving. The champion device based on this recycle strategy produced a PCE of 9.12% due to the suppressed halide separation and reduced defects.…”
Section: Htm‐free Normal All‐inorganic Pscsmentioning
confidence: 99%